Behavior Change of Darul Falah Senior High School Students After Attending Tabligh Akbar - Murharyana, Murharyana; Al Ayyubi, Ibnu Imam; Rohmatulloh, Rifqi; Suryana, Irfan (Dirasah International Journal of Islamic Studies, 2023)
Tabligh Akbar has become a tradition that is inherent and ingrained in Indonesian society, in which there are strings of holy verses of the Qur'an and chanting blessings accompanied by melodious Islamic tones, which add to the specialness. This study used a qualitative method with a descriptive approach and ethnographic research. The data sources were taken from respondents in the form of several Darul Falah SMA students in grades X, XI, and XII, in which they are teenagers who often participate in Tabligh Akbar activities in various places, using data analysis techniques including data collection, data reduction, data display, and conclusion drawings or verification. In this study, it was found that Darul Falah High School students were in their teens and took part in the Tabligh Akbar to find identity and experience during the transition period, so that there was a comparison between the experience of academics in schools and religious experience in society, because there were still students who had not fully entered the formal operational stage, but still in the transitional stage from the concrete to the formal operational stage, the doctrines that were assimilated in the Tabligh Akbar activities and accepted by students can be realigned or classified as good and bad indicators with true religious lessons.